Maternal Liver Damage Delays Meiotic Resumption in Bovine Oocytes through Impairment of Signalling Cascades Originated from Low p38MAPK Activity in Cumulus Cells. Issue 1 (17th September 2013) - Tanaka, H; Takeo, S; Monji, Y; Kuwayama, T; Iwata, H
Contents: The main objective of the present study is to investigate the molecular mechanism underlying the delay in progression of nuclear maturation in oocytes derived from cows with damaged livers (DL cows), which was previously reported. In present study, delayed progression of nuclear maturation of oocytes derived from DL cows relative to oocytes derived from cows with healthy livers (HL cows) was accompanied by low maturation promoting factor (MPF) activity (0.43 fold, p < 0.05). When cumulus cells were removed from cumulus‐oocyte complexes and the denuded oocytes were cultured, there was no difference in the progression of nuclear maturation between the two liver conditions. In addition, gap junctional communication (GJC) between the oocyte and cumulus cells was higher in DL cows than in HL cows at 3 and 7 h of in vitro maturation (IVM) (p < 0.05). Supplementation of IVM medium with epidermal growth factor (EGF) increased the ratio of germinal vesicle breakdown (GVBD) of oocytes derived from DL cows to the level seen in oocytes derived from HL cows. Additionally, the level of p38MAPK phosphorylation at 0 h of IVM was significantly lower in cumulus cells derived from DL cows than in cumulus cells derived from HL cows (HL cows, 53.5%; DL cows, 28.9%; p < 0.05). Thus, a low level of p38MAPK phosphorylation in cumulus cells induced slow GJC closure between oocyte and cumulus cells, which resulted in slow meiotic maturation of oocytes derived from DL cows.